Analysis of Disturbances in Large Power Systems: Case Study of the 1999 Marmara Earthquake - (:unkn) unknown (IEEE, 2008)
The earthquake, occurred on August 17, 1999 at 03:02 a.m. affected the northwest of Turkey. The region is very important for the Turkish Economy both in terms of production and consumption capacities. Failure occurred in the Marmara Region due to damage caused by the earthquake to the substations and power transmission lines located in the hardest-hit areas that affected the Turkish Power System as well a blackout was experienced throughout the country except those isolated fed areas. In this paper, analysis of disturbances on Turkish power system is simulated by MATLAB after the Marmara Earthquake. Voltage and frequency profiles of the region are shown in graphics.